2019
DOI: 10.1186/s12887-019-1842-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of underweight, overweight and obesity among Palestinian school-age children and the associated risk factors: a cross sectional study

Abstract: BackgroundChildhood obesity is rising in developed and developing countries, while childhood underweight is rising mainly in developing countries. Childhood underweight has been shown to increase a child’s risk of rapid weight gain. Overweight and obese children are more likely to become obese adults, which increases the risk of type-II diabetes and cardiovascular diseases. Studies concerning obesity among Palestinian children are scarce. The prevalence of obesity among Palestinian children has increased from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 32 publications
(38 reference statements)
0
32
0
Order By: Relevance
“…The prevalence of overweight/ obesity in our study was 25.3% in girls and 23.1% in boys. A previous cross-sectional study conducted among school-age Palestinian children reported that the prevalence of overweight and obesity was approximately 14.5% and 15.7%, respectively, which supports an accelerated increase in the prevalence of overweight/obesity (Al-Lahham et al, 2019). Similarly, findings from marginalized Palestinian schools in the West Bank showed that the 34% of adolescents were overweight or obese (85th percentile or over; Amer et al, 2019) and a systematic review of childhood obesity in the Middle East and North Africa (MENA) region concluded that the obesity rate in children and adolescents is rising rapidly (Farrag et al, 2017).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The prevalence of overweight/ obesity in our study was 25.3% in girls and 23.1% in boys. A previous cross-sectional study conducted among school-age Palestinian children reported that the prevalence of overweight and obesity was approximately 14.5% and 15.7%, respectively, which supports an accelerated increase in the prevalence of overweight/obesity (Al-Lahham et al, 2019). Similarly, findings from marginalized Palestinian schools in the West Bank showed that the 34% of adolescents were overweight or obese (85th percentile or over; Amer et al, 2019) and a systematic review of childhood obesity in the Middle East and North Africa (MENA) region concluded that the obesity rate in children and adolescents is rising rapidly (Farrag et al, 2017).…”
Section: Discussionmentioning
confidence: 63%
“…Family-based lifestyle changes, including decreasing total caloric intake, increasing physical activity and decreasing sedentary time, have been proposed as the cornerstone of weight management in children (Kumar & Kelly, 2017), and should be implemented in Palestinian children. Interestingly, a recent study on Palestinian children found that living in the city, maternal and paternal BMI, WC, modes of transport, and chocolate and sweet intake, were significantly associated with the BMI of children (Al-Lahham et al, 2019). Those authors concluded that the increased prevalence of childhood obesity might be due to the rapid urbanization and transition from conventional to western lifestyles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity can be assessed through BMI, waist circumference (WC), body fat percentage (BFP), and skin fold thickness (SFT). As evidenced in the literature, the anthropometric method shows a correlation between the factors [18,20,43]. Recently, the classification of obesity was reevaluated and validated again with the consideration of morbidity and mortality at population level.…”
Section: Assessment Methods Of Obesitymentioning
confidence: 97%
“…According to the framework, the basic causes including poverty, social condition, and political, economic, ecological, and other factors were the root reason for any form of malnutrition [13]. Different literature studies explicitly identified sociodemographic factors that were highly correlated with obesity, for example, older age [2,6], married (marital status) [14], low wealth index [6,10,[15][16][17], urban residency [6,10,16,18], being female [2,9], learning in private schools [2,9,19,20], easy accessibility of junk and fired or energy-dense foods and packed animal source foods due to free trade policy [2], rural to urban migration, replacement of local agribusiness with food retail [21], higher education level [6,7,22], and being pregnant [6,18]. In contrary to the previous findings, a study conducted among French women shows that having a higher income, a higher occupational class, and a higher educational level and having hot water at home reduce the occurrence of obesity [23] although the pathophysiology of hot water at home and obesity occurrence was not yet studied.…”
Section: Sociodemographic Factors Based On United Nationsmentioning
confidence: 99%